探析大學圖書館員工作滿意、工作自主性與工作績效之關係模式 The Study of Relationship between Job Satisfaction, Job Autonomy and Job Performance of University Librarians - Yu-Ping Peng (Jiàoyù zīliào yǔ túshūguǎn xué, 2012)
大學圖書館面臨人力數量不足之經營難題，管理者需要激勵館員持續提升工作績效與負擔額外工作的意願，以提升圖書館組織績效。本研究蒐集大學圖書館員問卷資料，運用結構方程模式(structural equation modeling, SEM)，建構並驗證大學圖書館員工作滿意與工作績效面向層次之關係模式，結果發現館員工作滿意程度愈高，其工作績效程度愈高，工作自主性對上述關係具有顯著正向調節效果。另進行競爭分析及差異性分析，最後提出管理建議。 Manpower shortage is the biggest management dilemma of university libraries in Taiwan. University libraries require librarians to continuously increase their performance capabilities to keep up with rapidly changing environments and meet changing customers’ need. Based on a structural equation modeling, this study examines the relationship between job satisfaction and job performance at facet level for the university librarians in Taiwan. Results indicated that job satisfaction is positively related to job performance. Findings indicated that job autonomy moderates the above relationship. The study also uses competing statistical models and difference analysis. Finally, the study provides some managerial implications for the librarianship profession.